The Effect of Workload and Internal Communication on Employee Performance of BPS Kubu Raya Regency with Work Motivation as Mediation: PENGARUH BEBAN KERJA DAN KOMUNIKASI INTERNAL TERHADAP KINERJA PEGAWAI BPS KABUPATEN KUBU RAYA DENGAN MOTIVASI KERJA SEBAGAI MEDIASI - Priyatama, Andika; Pratiwi, Windi; Ariffin, Muchammad; Aisyah, Aisyah (Jurnal Ecoment Global, 2025)
This study aims to examine and analyze the effect of workload and internal communication on the performance of employees at the Central Bureau of Statistics (BPS) of Kubu Raya Regency, with work motivation as a mediating variable. The research employed a quantitative approach with an associative-causal design, involving all 30 employees as the sample using a saturated sampling technique. Data were collected through questionnaires, interviews, and literature reviews, and analyzed using multiple regression and the Sobel test with SPSS 31. The findings reveal that workload and internal communication significantly and positively influence work motivation, while workload and internal communication both have a significant negative effect on performance. Furthermore, work motivation does not mediate the relationship between workload and performance but significantly mediates the effect of internal communication on performance. This study contributes to the literature by highlighting the mediating role of work motivation and provides practical implications for improving performance through proportional workload management, enhancing the quality of internal communication, and strengthening work motivation.